2007
DOI: 10.1021/ac0618730
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing TiO2-Based Phosphopeptide Enrichment for Automated Multidimensional Liquid Chromatography Coupled to Tandem Mass Spectrometry

Abstract: An automated online multidimensional liquid chromatography system coupled to ESI-based tandem mass spectrometry was used to assess the effectiveness of TiO 2 in the enrichment of phosphopeptides from tryptic digests of protein mixtures. By monitoring the enrichment of phosphopeptides, an optimized set of loading, wash, and elution conditions were realized for TiO 2 . A comparison of TiO 2 with other resins used for phosphopeptide enrichment, Fe(III)-IMAC and ZrO 2 , was also carried out using tryptic digests o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 32 publications
1
115
0
Order By: Relevance
“…Winkler and Marme reported that another commercial titania (Sachtopore from Sachtleben Chemie GmbH) was also anatase form. 34 In this study, we chose Titansphere based on the results of a comparison between these commercial beads, 29 and prepared rutile beads by the calcination method according to Tani et al 35 By heating Titansphere at 800˚C for 2 h, we successfully obtained rutile beads, as shown in Fig. 1B.…”
Section: Comparison Of 800˚c-calcined Titania With Commercial Titanspmentioning
confidence: 99%
See 1 more Smart Citation
“…Winkler and Marme reported that another commercial titania (Sachtopore from Sachtleben Chemie GmbH) was also anatase form. 34 In this study, we chose Titansphere based on the results of a comparison between these commercial beads, 29 and prepared rutile beads by the calcination method according to Tani et al 35 By heating Titansphere at 800˚C for 2 h, we successfully obtained rutile beads, as shown in Fig. 1B.…”
Section: Comparison Of 800˚c-calcined Titania With Commercial Titanspmentioning
confidence: 99%
“…17,19,24,28,29 However, no system has yet been applied to real complex samples, such as cell lysates, although recently Cantin et al analyzed a moderately complex sample with a titania column-trap column system. 29 The reason for the failure to achieve practical application is mainly that the dynamic range between phosphorylated and non-phosphorylated peptides is much wider in real samples, and this results in poor identification of phosphopeptides.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is chemical reaction-based methods which include beta-elimination of the phosphate group and subsequent introduction of an affinity tag [11], and then captured by beads and released [12]. The second one is chromatography based methods which include affinity chromatography with immobilized metal ions (IMAC) [13][14][15][16][17][18][19][20][21][22][23], metal oxides such as titanium dioxide (TiO 2 ) and zirconium dioxide (ZrO 2 ) [24][25][26][27][28][29][30][31], and strong cation exchange chromatography (SCX) [32][33][34][35]. Among all of these methods, IMAC with Fe 31 is the most popular technique for the enrichment of phosphorylated peptides.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, phosphoramidate chemistry has been developed to allow coupling phosphopeptides to a dendrimer (Tao et al, 2005;Bodenmiller et al, 2007c). The different enrichment strategies, IMAC and TiO 2 (Cantin et al, 2007;Liang et al, 2007;Marcantonio et al, 2008;Wilson-Grady, Villen, & Gygi, 2008), as well as phosphoramidate chemistry (Bodenmiller et al, 2007b), provide distinct but overlapping sets of phosphopeptides. Phosphotyrosine-containing peptides could be handled differently and targeted more specifically: the availability of highly specific antibodies that recognize this phosphomotif allowed the large-scale affinity purification of pTyrcontaining proteins/peptides.…”
Section: Purification Of Phosphopeptidesmentioning
confidence: 99%